Uniform combined reconstruction of multichannel 7T knee MRI receive coil data without the use of a reference scan. Issue 5 (19th February 2019) - Chebrolu, Venkata Veerendranadh; Kollasch, Peter D.; Deshpande, Vibhas; Grinstead, John; Howe, Benjamin M.; Frick, Matthew A.; Fagan, Andrew J.; Benner, Thomas; Heidemann, Robin M.; Felmlee, Joel P.; Amrami, Kimberly K.
Abstract : Background: MR image intensity nonuniformity is often observed at 7T. Reference scans from the body coil used for uniformity correction at lower field strengths are typically not available at 7T. Purpose: To evaluate the efficacy of a novel algorithm, Uniform Combined Reconstruction (UNICORN), to correct receive coil‐induced nonuniformity in musculoskeletal 7T MRI without the use of a reference scan. Study Type: Retrospective image analysis study. Subjects: MRI data of 20 subjects was retrospectively processed offline. Field Strength/Sequence: Knees of 20 subjects were imaged at 7T with a single‐channel transmit, 28‐channel phased‐array receive knee coil. A turbo‐spin‐echo sequence was used to acquire 33 series of images. Assessment: Three fellowship‐trained musculoskeletal radiologists with cumulative experience of 42 years reviewed the images. The uniformity, contrast, signal‐to‐noise ratio (SNR), and overall image quality were evaluated for images with no postprocessing, images processed with N4 bias field correction algorithm, and the UNICORN algorithm. Statistical Tests: Intraclass correlation coefficient (ICC) was used for measuring the interrater reliability. ICC and 95% confidence intervals (CIs) were calculated using the R statistical package employing a two‐way mixed‐effects model based on a mean rating (k = 3) for absolute agreement. The Wilcoxon signed‐rank test with continuity correction was used for analyzing the overall image quality scores. Results: UNICORN was preferred among the three methods evaluated for uniformity in 97.9% of the pooled ratings, with excellent interrater agreement (ICC of 0.98, CI 0.97–0.99). UNICORN was also rated better than N4 for contrast and equivalent to N4 in SNR with ICCs of 0.80 (CI 0.72–0.86) and 0.67 (CI 0.54–0.77), respectively. The overall image quality scores for UNICORN were significantly higher than N4 ( P < 6 × 10 ‐13 ), with good to excellent interrater agreement (ICC 0.90, CI 0.86–0.93). Data Conclusion: Without the use of a reference scan, UNICORN provides better image uniformity, contrast, and overall image quality at 7T compared with the N4 bias field‐correction algorithm. Level of Evidence: 4 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2019;50:1534–1544.